Interdisciplinary Perspectives on Folklore: Arts-Based Research (ABR) in The Novelization of Traditional Tales to Strengthen Character Education Through Language and Literature Teaching - Youpika, Fitra; Sumiyadi, Sumiyadi; Permadi, Tedi; Sunendar, Dadang; Syaputra, Juni (Universitas Negeri Makassar, 2025)
The study aims to elucidate the interdisciplinary perspective of folklore studies and arts-based research (ABR), focusing on the novelization of traditional stories to strengthen character education. An interdisciplinary perspective on language, literature, art, and education studies is employed to investigate how traditional folklore can be re-created through creative literary endeavors. Using an ABR qualitative research design, preceded by realist ethnographic research and in-depth character content analysis, this study explores the complexities of transforming oral traditions into written narratives, emphasizing the role of artistic interpretation in preserving cultural heritage and values. The steps of ABR are carried out through comparative data, literature review, and analysis of art practices of the selected traditional stories for their new adaptation. The results show that the folklore (legend) of Raden Alit has three variants. The variants teach about the values of religiousness, nationalism, independence, cooperation, and integrity. The variants of the Raden Alit folklore (legend) can be combined and transformed into a novel (didactic literature) through the six stages of the creative process of fiction-based research (FBR) design, which is part of arts-based research. The implications of this research are essential for socio-cultural in the contemporary context because it is relevant to the preservation and dissemination of cultural heritage. By integrating insights from folklore studies, literary analysis, and artistic practice, this study contributes to an emerging interdisciplinary research field. It offers valuable insights into the transformative potential of arts-based approaches to preserving and disseminating traditional folklore.